2014
DOI: 10.1007/s11906-014-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Renal Denervation in Resistant Hypertension

Abstract: Resistant hypertension, defined as inadequate blood pressure control despite three or more antihypertensive medications at maximally tolerated doses, is strongly linked to increased cardiovascular morbidity and mortality. Increased renal afferent and efferent sympathetic activity carried by nerves which arborize the adventitia of the renal arteries, appears to be central to the pathobiology of resistant hypertension. Historical experience indicates that surgical denervation and/or sympathectomy often dramatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…15,36 It has been noted in the primary study report that the role of the interventionalist was not a key factor in BP outcomes. 13 In a subsequent, formal analysis assessing the changes in office, ambulatory, and home SBPs associated with the number of ablation attempts (<9 to >14) or the ablation pattern (0, 1 [either right or left side], or 2 [both sides] four-quadrant ablations), Kandzari and coworkers from the trial showed an important trend suggesting that more complete radiofrequency ablation yielded greater denervation that translated to more marked BP-lowering effects.…”
Section: Expertise Of the Operator In Device Trialsmentioning
confidence: 98%
See 1 more Smart Citation
“…15,36 It has been noted in the primary study report that the role of the interventionalist was not a key factor in BP outcomes. 13 In a subsequent, formal analysis assessing the changes in office, ambulatory, and home SBPs associated with the number of ablation attempts (<9 to >14) or the ablation pattern (0, 1 [either right or left side], or 2 [both sides] four-quadrant ablations), Kandzari and coworkers from the trial showed an important trend suggesting that more complete radiofrequency ablation yielded greater denervation that translated to more marked BP-lowering effects.…”
Section: Expertise Of the Operator In Device Trialsmentioning
confidence: 98%
“…6,13,15 In both pre-specified and post-hoc exploratory analyses of the SYMPLICITY HTN-3 trial data, changes in medication prescriptions, procedural technique regarding distribution and number of ablations, and differential outcomes among ethnic subgroups were identified as potential confounders. 16 Based on all the aforementioned information and the failure of the first randomized and sham-procedure controlled trial in RDN therapy, the consensus of the group participating in the forum was that this interesting trial did not represent a failure of the RDN field in general, but rather underscored the need to determine how investigations should proceed in the area for future development of device-based therapies in various forms of systemic hypertension.…”
Section: Background Informationmentioning
confidence: 99%
“…In animal models, the sham RDN procedure has been shown to have an effect, 12 and while a placebo effect or increased adherence to antihypertensive treatment 4,5 is not of direct relevance, the impact of the sham surgery should be determined in a comparably succinct and thorough fashion as undertaken in the current study. It should also be noted that the study was performed in young, healthy normotensive animals, and as the authors correctly identify, it remains to be determined whether age or concurrent disease status influences the rate or functionality of nerve regrowth.…”
mentioning
confidence: 99%
“…Their work is timely given the failure of the only appropriately powered, blinded, sham-controlled RDN clinical study to meet its primary end points, 2,3 and indeed the future of the technique as the panacea for the treatment of resistant hypertension is now being questioned. 4,5 Although issues of procedural competency and suboptimal denervation have been raised, 6 it is now more important than ever for the basic mechanisms underlying RDN to be clarified because specific patient cohorts may still show better responsiveness to therapy, 5 and secondary benefits of RDN in conditions such as diabetes mellitus, chronic kidney disease, and heart failure are still under investigation. 4 Whether primary beneficial effects are because of removal of afferent (sensory), efferent (sympathetic), or both components of the renal nerve also remains to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation